2019
DOI: 10.1016/j.jadohealth.2018.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Trends in Adolescent Smoking in Finland From 2000 to 2015

Abstract: Smoking is a significant cause of morbidity and mortality worldwide. In the past decades, the prevalence of adolescent smoking has decreased in industrial countries. However, whether the decreasing trend can be seen across all socioeconomic groups is unknown. The aim of this study was to examine time trends in adolescent smoking according to the socioeconomic status among Finnish adolescents between 2000 and 2015. Methods: A population-based school survey was conducted biennially among 14-to 16-year-old Finns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
2
14
0
1
Order By: Relevance
“…Our findings were partly consistent with a Slovak study [ 14 ] that found that the socioeconomic differences in smoking for parental education decreased among boys and increased among girls over time. However, some previous studies showed that time trends in smoking differences between familial SES groups have persisted or increased over time [ 10 , 11 , 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings were partly consistent with a Slovak study [ 14 ] that found that the socioeconomic differences in smoking for parental education decreased among boys and increased among girls over time. However, some previous studies showed that time trends in smoking differences between familial SES groups have persisted or increased over time [ 10 , 11 , 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Finnish study created a cumulative socioeconomic adversity variable which combined parental education, parental unemployment, and family structure and showed that the overall prevalence of adolescent smoking decreased between 2000 and 2015. However, no similar changes were observed among adolescents with most socioeconomic adversities, which resulted in the increased relative socioeconomic differences over time [ 11 ]. On the other hand, a German study which assessed parental SES (family affluence) and student’s own SES (school type) found that both socioeconomic differences in adolescent smoking remained unchanged between 1994 and 2002 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trend merokok pada remaja menjadi masalah Internasional, akibat yang dapat ditimbulkan dari rokok menjadi penyumbang peningkatan kematian di dunia (Knaappila, Marttunen, Fröjd, Lindberg, & Kaltiala-Heino, 2019). Kasus merokok banyak dijumpai di negara menengah atas dan berpenghasilan rendah, salah satunya Indonesia (WHO, 2017).…”
Section: Pendahuluanunclassified
“…To keep track of mental health in the population and to monitor the effectiveness of interventions on mental health disorders, data on the time trends of these disorders are needed. According to time trend studies in the 2000s and 2010s, mental health problems among Finnish adolescents have not increased (15)(16)(17)(18)(19). Instead, the demand for mental health services, especially for the treatment of depression and anxiety disorders, has recently increased among adolescents.…”
Section: Introductionmentioning
confidence: 99%